2009
DOI: 10.1261/rna.1699809
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative miRNA expression analysis: Comparing microarrays with next-generation sequencing

Abstract: Recently, next-generation sequencing has been introduced as a promising, new platform for assessing the copy number of transcripts, while the existing microarray technology is considered less reliable for absolute, quantitative expression measurements. Nonetheless, so far, results from the two technologies have only been compared based on biological data, leading to the conclusion that, although they are somewhat correlated, expression values differ significantly. Here, we use synthetic RNA samples, resembling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
123
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 12 publications
5
123
0
2
Order By: Relevance
“…Omission of ''obsolete'' or ''not_designed_for_hsa'' Exiqon probes resulted in minimal changes to these numbers (60.2 in optimal fold-change cutoff and 60.04 in TP/TN rates; data not shown). The low sensitivity (TP) of GAseq contradicts the commonly expressed expectation of digital miRNA profiling and was also recently reported in a comparative study using a pool of synthetic RNAs (Willenbrock et al 2009). …”
Section: Correlation With Qpcr Resultsmentioning
confidence: 91%
“…Omission of ''obsolete'' or ''not_designed_for_hsa'' Exiqon probes resulted in minimal changes to these numbers (60.2 in optimal fold-change cutoff and 60.04 in TP/TN rates; data not shown). The low sensitivity (TP) of GAseq contradicts the commonly expressed expectation of digital miRNA profiling and was also recently reported in a comparative study using a pool of synthetic RNAs (Willenbrock et al 2009). …”
Section: Correlation With Qpcr Resultsmentioning
confidence: 91%
“…Previously, it has been reported that absolute microarray expression measures correlate better than deep-sequencing data with RNA samplecontent when synthetic samples mimicking the human miRNA pool are used (Willenbrock et al, 2009). However, the correlation between absolute miRNA expression values determined by microarrays and by next-generation sequencing may differ strongly depending on the platform used for microarray profiling (Git et al, 2010), or on the algorithm used for processing of sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several investigations [13][14][15] into the biases that affect the accuracy with which RNA-Seq represents the absolute abundance of a given transcript as measured by high precision approaches such as Taqman RT-PCR [16]. It has been shown that these abundance measures are prone to biases correlated with the nucleotide composition [14,17] and length of the transcript [1,18].…”
mentioning
confidence: 99%